A study on solidification kinetics of gelatin using avrami model - Mohd Nor, Nurul Hazwani (2018)
The solidification of gelatin is important in many applications especially preparation and handling of food nowadays. This is because many applications of using gelatin in the product and beneficial. This work aims on studying the effects of process parameters on solidification kinetics of gelatin utilizing Avrami model and determines the quality of gelatin by bloom test or gel strength. The effect of different parameters used in this work are different cooling temperatures, different concentrations, different sample sizes, different amount of sugars added and different acid concentrations added. The solidification of gelatin was determined gravimetrically and analyzed using Avrami equation. The results indicate that lower cooling temperature achieves 100% of solidification percentage in shorter time. The rate of solidification growth increases when gelatin concentrations increase while the bigger sample size of gelatin used retards the solidification of gelatin and takes a longer time to solidify. In addition, the more amount of sugar increases rate of solidification. The increase of acid concentrations added into gelatin solution also causes slow growth of solidification. Therefore, the n value increases as K value decreasing. The less concentrated of the gelatin solution, gel strength decreases while the higher amount of addition of sugar also decreases the gel strength of gelatin which influences the quality of gelatin. Hence, cooling temperature, sample concentration, sample size, addition of sugar and acid gives effect on solidification growth rate of gelatin.